Health Coaching Implementation using CERDIK Strategy to Improve Health and Prevent Osteoporosis in Mothers - Lestari, Wahyuni Tri; Kristiawati, Kristiawati; Delfianti, Rezi (Yayasan Inspirasi El Burhani, 2026)
Introduction: Women are at a higher risk of osteoporosis than men, particularly after menopause due to decreased estrogen levels, which contribute to bone mass loss. Osteoporosis in women deserves serious attention, given their important role in families and society. The majority of target partners are over 35 years old and there are several elderly mothers. Providing health coaching using the CERDIK strategy offers an effective approach to preventing osteoporosis in the population. Objective: This community service aims to enhance knowledge and skills in osteoporosis prevention, improve health status and fitness by optimizing exercise activities, and provide comprehensive guidelines for osteoporosis prevention to women's groups. Method: This community service conducted in September 2025 involving 23 participants from RT 02 Wadungasih Buduran-Sidoarjo, consisted of five stages. The activities were carried out using an educational and participatory approach through health examinations, interactive lectures, discussions, and demonstrations of osteoporosis exercises. Pre- and post-intervention evaluations were conducted using questionnaires and health assessments. Health assessments including measurements of blood pressure, pulse rate, and body temperature, were conducted 30 minutes before-after the osteoporosis exercise. Pre-post test data were analyzed using SPSS software with the Wilcoxon Signed-Rank test. Result: There was a significant increase in knowledge (p = 0.005) and skills (p = 0.000) following the implementation of health coaching and osteoporosis exercise. The findings of this community service program indicate that health coaching and osteoporosis exercise are effective in enhancing participants’ knowledge and skills related to osteoporosis prevention. Conclusion: Implementing health coaching as CERDIK (Periodic health checks, Smoking cessation, Regular physical activity, Balanced diet, Adequate rest, and Stress management) proved effective in raising knowledge and abilities. Health coaching combined with osteoporosis exercise represents a comprehensive and sustainable preventive strategy for promoting health and preventing osteoporosis.